2006
DOI: 10.1167/iovs.05-0869
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Axial Length and Intraocular Pressure Fluctuations in Human Eyes

Abstract: Both axial length and IOP fluctuate during the day much of the time in most subjects. However, diurnal IOP fluctuations do not appear to cause diurnal axial length fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 18 publications
5
48
0
Order By: Relevance
“…Studies of diurnal ocular variations of axial length in humans have shown that the eye is typically longest during the day and shortest at night, and these variations range in magnitude from 25 to 46 µm over 24 hours (Stone et al, 2004;Wilson et al, 2006;Read et al, 2008;Chakraborty et al, 2011). Initial human studies showed that diurnal variations were not consistent on all measurement days (Stone et al, 2004;Wilson et al, 2006), but it is possible that seasonal variations could have influenced these results (Chakraborty et al, 2011), as the measurement days were separated by weeks and sometimes months in these studies.…”
Section: Diurnal Ocular Variationsmentioning
confidence: 92%
See 4 more Smart Citations
“…Studies of diurnal ocular variations of axial length in humans have shown that the eye is typically longest during the day and shortest at night, and these variations range in magnitude from 25 to 46 µm over 24 hours (Stone et al, 2004;Wilson et al, 2006;Read et al, 2008;Chakraborty et al, 2011). Initial human studies showed that diurnal variations were not consistent on all measurement days (Stone et al, 2004;Wilson et al, 2006), but it is possible that seasonal variations could have influenced these results (Chakraborty et al, 2011), as the measurement days were separated by weeks and sometimes months in these studies.…”
Section: Diurnal Ocular Variationsmentioning
confidence: 92%
“…Initial human studies showed that diurnal variations were not consistent on all measurement days (Stone et al, 2004;Wilson et al, 2006), but it is possible that seasonal variations could have influenced these results (Chakraborty et al, 2011), as the measurement days were separated by weeks and sometimes months in these studies. However, the effects of seasons and light exposure upon ocular diurnal variations have not been studied previously in humans.…”
Section: Diurnal Ocular Variationsmentioning
confidence: 95%
See 3 more Smart Citations